Gadget Use and Social-Emotional Growth: Does It Connect or Detach Children from Their Peers? - Hajar, Siti; Puspita, Yenda; Sa'ida, Amin Yusi Nur; Fauziddin, Moh (Atfaluna Journal of Islamic Early Childhood Education, 2025)
This study examines the relationship between gadget use and the social and emotional development of early childhood. Concerns over the increasing intensity of gadget use in early childhood and its potential negative impact on social interaction and emotional regulation prompted this quantitative correlational study involving 25 children aged 5-6 years at Pembina Kindergarten, Kampar, selected using a total sampling technique. Data were collected through a Likert-scale questionnaire completed by parents and teachers, accompanied by documentation. Data analysis, conducted using SPSS 25.0, included a nonparametric Spearman's Rank correlation test and the coefficient of determination. The results showed a significant negative correlation (r = -0.639, p = 0.001 < 0.05) between gadget use and social and emotional development, indicating a strong association. Furthermore, gadget use explained 41.8% (Adjusted R² = 0.418) of the variation in children's social and emotional development, with the remaining variation related to other factors such as parenting styles, environment, and external social interactions. These findings emphasize the need for wise gadget management to support optimal social and emotional growth. Longitudinal studies with larger, more diverse samples could help better understand the long-term impact of gadget use on early childhood and are recommended for further research. Qualitative research could also be conducted to explore the role of parenting styles and the family environment in moderating the relationship between gadget use and children's social and emotional development.